Absence of Cultural Awareness Training in International Non-Governmental Organizations. Issue 5 (16th September 2019) - Hart, Alexander; Toma, Mariana; Issa, Fadi; Ciottone, Gregory R.
Abstract: Introduction: Cultural awareness can be defined as an understanding of the differences that exist between cultures. This understanding is a crucial first step towards the development of cultural sensitivity, a willingness to accept those differences as having equal merit, and becoming operationally effective when working within different cultures. The benefits of cultural awareness have become apparent in recent decades, including within governments, militaries, and corporations. Many organizations have developed cultural awareness training for their staffs to improve cross-cultural cooperation. However, there has not been a large movement toward cultural sensitivity training among non-governmental organizations (NGOs) who provide aid globally, across a number of countries and cultures. Cultural awareness can be a useful tool which enables an NGO to better serve the populations with which they engage. Problem: The goal of this study was to evaluate the presence of cultural awareness training for employees and volunteers working within international NGOs. Methods: Ten of the largest international NGOs were identified. Their websites were evaluated for any mention of training in cultural awareness available to their employees and volunteers. All ten were then contacted via their public email addresses to find out if they provide any form of cultural awareness training. Results: Of the ten NGOs identified, none had any publicly available cultural awareness training on their websites. One NGO dealt with cultural awareness by only hiring local staff, who were already a part of the prevalent culture of the area. None of the others who responded provided any cultural awareness training. Conclusion: Cultural awareness is a vital tool when working internationally. Large NGOs, which operate in a wide-range of cultures, have an obligation to act in a culturally aware and accepting manner. Most large NGOs currently lack a systematic, robust cultural awareness training for their employees and volunteers.